Relationship of Family Support and Self-Efficacy with Postpartum Depression among Postpartum Mothers - Cucu Eka Pertiwi; Ni Ketut Alit Armini; Eka Mishbahatul Mar’ah Has (Pediomaternal Nursing Journal, 2021)
Introduction: The postpartum period is a challenging transition for postpartum mothers. The existence of major changes can make mothers experience mood disorders such as postpartum depression. The purpose of this study was to determine the relationship between family support and self-efficacy with the incidence of postpartum depression.Methods: This study uses a cross-sectional design. The population in this study was postpartum mothers. The sample involved 97 respondents using a consecutive sampling technique. The inclusion criteria in this study were postpartum mothers with 1-4 month periods. The exclusion criteria used were postpartum mothers with severe mental disorders. Data were collected using Sources of Social Support Scale questionnaires, Perceived Maternal Parental Self Efficacy, and Edinburgh Postpartum Depression Scale. The analysis uses the spearman rho test statistical test.Results: The results showed there was a relationship between family support and postpartum depression (p = 0.000; r = -0.364) and there was a relationship between self-efficacy and the incidence of postpartum depression (p = 0.000; r = -0.355).Conclusion: The higher the family support and self-efficacy, the lower the chance of postpartum depression. Postpartum mothers who get high family support will feel cared for, loved, and can share the burden so they can reduce stress which ultimately reduces postpartum depression. Postpartum mothers who have high self-efficacy tend to regard the task difficulties that she faces as an obstacle rather than as a threat that leads to the emergence of depression.